Adaptive time discontinuous Galerkin method for numerical modelling of wave propagation in shell and 3D structures - Tie, Bing; Aubry, Denis (European Journal of Computational Mechanics, 2006)
This paper presents an adaptive time discontinuous Galerkin method tailored to the numerical modelling of the wave propagation phenomena through shell and 3D structures. To achieve a reliable and efficient numerical implementation, several important computational issues concerning adaptive computation are discussed, namely the variable transfer between unmatched adaptively refined finite element meshes and the improvement of the convergence of the implicit dynamic solver by using a frequency dependent relaxation coefficient. Numerical examples of large-sized engineering structures are given to illustrate the interest and efficiency of the presented method.